Mature and progenitor endothelial cells perform angiogenesis also under protease inhibition: the amoeboid angiogenesis - Chillà, Anastasia (J Exp Clin Cancer Res, 2018)
BACKGROUND: Controlling vascular growth is a challenging aim for the inhibition of tumor growth and metastasis. The amoeboid and mesenchymal types of invasiveness are two modes of migration interchangeable in cancer cells: the Rac-dependent mesenchymal migration requires the activity of proteases; the Rho-ROCK-dependent amoeboid motility is protease-independent and has never been described in endothelial cells. METHODS: A cocktail of physiologic inhibitors (Ph-C) of serine-proteases, metallo-proteases and cysteine-proteases, mimicking the physiological environment that cells encounter during their migration within the angiogenesis sites was used to induce amoeboid style migration of Endothelial colony forming cells (ECFCs) and mature endothelial cells (ECs). To evaluate the mesenchymal-ameboid transition RhoA and Rac1 activation assays were performed along with immunofluorescence analysis of proteins involved in cytoskeleton organization. Cell invasion was studied in Boyden chambers and Matrigel plug assay for the in vivo angiogenesis. RESULTS: In the present study we showed in both ECFCs and ECs, a decrease of activated Rac1 and an increase of activated RhoA upon shifting of cells to the amoeboid conditions. In presence of Ph-C inhibitors both cell lines acquired a round morphology and Matrigel invasion was greatly enhanced with respect to that observed in the absence of protease inhibition. We also observed that the urokinase-plasminogen-activator (uPAR) receptor silencing and uPAR-integrin uncoupling with the M25 peptide abolished both mesenchymal and amoeboid angiogenesis of ECFCs and ECs in vitro and in vivo, indicating a role of the uPAR-integrin-actin axis in the regulation of amoeboid angiogenesis. Furthermore, under amoeboid conditions endothelial cells seem to be indifferent to VEGF stimulation, which induces an amoeboid signaling pattern also in mesenchymal conditions. CONCLUSION: Here we first provide a data set disclosing that endothelial cells can move and differentiate into vascular structures in vitro and in vivo also in the absence of proteases activity, performing a new type of neovascularization: the “amoeboid angiogenesis”. uPAR is indispensable for ECs and ECFCs to perform an efficient amoeboid angiogenesis. Therefore, uPAR silencing or the block of its integrin-interaction, together with standard treatment against VEGF, could be a possible solution for angiogenesis inhibition. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-018-0742-2) contains supplementary material, which is available to authorized users.